Modeling the Fate of Toluene in a Chamber with Alfalfa Plants: 2. Numerical Results and Comparison Study - M. Narayanan; J. C. Tracy; L. C. Davis; L. E. Erickson (Journal of Hazardous Substance Research, 1998)
Investigations were conducted in a chamber to study the role of alfalfa plants in bioremediating toluene. Modeling and experimental results indicate that in situ bioremediation of toluene in the presence of plants is feasible and economical. This is primarily due to evapotranspiration which greatly enhances the vertical transport of dissolved contaminants from the saturated zone to the rhizosphere, thereby increasing the possibility of aerobic degradation. The fate of toluene was simulated and monitored for groundwater contaminated with toluene at saturated concentrations. FT-IR instrumentation was used to monitor toluene in the headspace gas of the vegetated chamber. Overall mass balance, based on groundwater and headspace measurements, indicated about 75% loss or biodegradation of toluene from the chamber during steady state. Evolution of significant amounts of CO2 accounted for mineralization of toluene. Simulation results predicted toluene biodegradation in the unsaturated zone where both oxygen and toluene were present. Dispersion processes in the soil were characterized by bromide tracer analysis. Predictions from simulations were compared with the water content and toluene concentrations measured in the chamber.
Keywords: biodegradation; toluene; gas phase diffusion; phytoremediation; soil; alfalfa